Determinan Kejadian Gizi Buruk Balita di Kelurahan Oesapa Kota Kupang - Ester B. Tameno; Marylin S. Junias; Sarci M. Toy (Universitas Malahayati Lampung, 2023)
ABSTRACT One of the nutritional problems that still occurs in the community is the problem of under-five malnutrition. WHO data in 2018 showed that around 49 million children under five were malnourished. The proportion of poor and less nutritional status nationally is equal to (17,7%). NTT Province ranks first at 29.5%. The problem of malnutrition under five is caused by direct or indirect risk factors. Maternal nutrition knowledge, poor parenting and unqualified clean water can affect the nutritional status of children under five. Low family income will lead to a lack of food supplies in the family. This study aims to determine the relationship between maternal nutrition knowledge, parenting feeding patterns, family income and availability of clean water to the incidence of under-five malnutrition in Oesapa Village, Kupang City in 2022This research was a case control study. A total sample of 40 was selected that consisted of 20 cases and 20 controls. Data collection techniques with interviews and observations. Data analysis used descriptive and bivariate with chi-square test. Variables associated with the incidence of under-five malnutrition were maternal nutrition knowledge (p= 0,000; OR = 17,000), parenting and feeding patterns (p= 0,003; OR = 13,500), and family income (p= 0,002; OR = 12,000), while the availability of clean water (p= 0.449; OR = 2.429) was found unrelated with the incidence of under-five malnutrition. In conclusion, the availability of clean water is not related to the incidence of under-five malnutrition, while the other three variables studied are related. So, to prevent under-five malnutrition, it is necessary for mothers to take active action in seeking information on nutritious food, cultivating local food to increase family income and food supply and keep water clean. Further research needs to develop other variables that were not examined by researchers, namely food availability in the family and history of low birth weight babies. Researchers hope that mothers are active in seeking information about nutritious foods, utilizing existing local food to increase family income and food supply so that they are able to serve healthy nutritious food to families, especially toddlers. In addition, keep the water clean by treating drinking water properly so that it does not become a source of spreading disease. Keywords: Toddlers, Malnutrition, Income, Knowledge of Nutrition, Parenting ABSTRAK Salah satu masalah gizi yang masih terjadi di kalangan masyarakat adalah masalah gizi buruk balita. Data WHO tahun 2018 menunjukkan sekitar 49 juta balita mengalami gizi kurang. Proporsi status gizi buruk dan kurang secara Nasional yaitu sebesar (17,7%). Provinsi NTT menempati urutan pertama yaitu sebesar 29,5%. Masalah gizi buruk balita disebabkan oleh faktor risiko secara langsung maupun tidak langsung. Pengetahuan gizi ibu yang rendah, pola asuh pemberian makan yang kurang dan air bersih yang tidak memenuhi syarat dapat berpengaruh terhadap status gizi balita. Pendapatan keluarga yang rendah akan menyebabkan kurangnya persediaan pangan dalam keluarga. Penelitian ini bertujuan untuk mengetahui hubungan antara pengetahuan gizi ibu, pola asuh pemberian makan, pendapatan keluarga dan ketersediaan air bersih terhadap kejadian gizi buruk balita di Kelurahan Oesapa Kota Kupang tahun 2022. Metode penelitian ini adalah case control. Sampel berjumlah 40 orang terdiri dari 20 kasus dan 20 kontrol. Teknik pengumpulan data dengan wawancara dan observasi. Analisis data yang digunakan adalah deskriptif dan bivariat menggunakan uji chi-square. Hasil penelitian ini menunjukkan pengetahuan gizi ibu berhubungan dengan kejadian gizi buruk balita (p=0,000; OR=17,000), pola asuh pemberian makan (p=0,003; OR=13,500), dan pendapatan keluarga (p=0,002; OR=12,000), sedangkan ketersediaan air bersih (p=0,449; OR=2,429) ditemukan tidak berhubungan dengan kejadian gizi buruk balita. Kesimpulannya, ketersediaan air bersih tidak berhubungan kejadian gizi buruk balita sedangkan ketiga variabel lainnya yang diteliti berhubungan. Maka, untuk mencegah gizi buruk balita diperlukan tindakan aktif ibu dalam mencari informasi makanan bergizi, membudidayakan pangan lokal untuk menambah pendapatan dan pasokan pangan keluarga serta menjaga air tetap bersih. Penelitian selanjutnya perlu mengembangkan variabel lain yang tidak diteliti oleh peneliti yaitu ketersediaan pangan dalam keluarga dan riwayat BBLR. Peneliti berharap ibu aktif dalam mencari informasi mengenai makanan-makanan yang bergizi, memanfaatkan pangan lokal yang ada untuk menambah pendapatan dan pasokan pangan keluarga sehingga mampu dalam menghidangkan makanan yang bergizi sehat kepada keluarga terkhususnya balita. Selain itu, menjaga air tetap bersih dengan mengolah air minum dengan tepat agar tidak menjadi sumber penyebaran penyakit. Kata Kunci: Balita, Gizi Buruk, Pendapatan, Pengetahuan Gizi, Pola Asuh